Frequency of genetic polymorphisms of COX1, GPIIIa and P2Y1 in a Chinese population and association with attenuated response to aspirin. (June 2007) - Li, Qing; Chen, Bi-Lian; Ozdemir, Vural; Ji, Wei; Mao, Yan-Mei; Wang, Lian-Ci; Lei, Hei-Ping; Fan, Lan; Zhang, Wei; Liu, Jie; Zhou, Hong-Hao
Background: Aspirin is a frequently prescribed drug for primary and secondary prevention of myocardial infarction, stroke and cardiovascular death. However, aspirin resistance may affect up to 45% of the population. Little is known on the role of genetic factors that contribute to resistance or augmented response to aspirin in different human populations.Methods: In a large sample of nonsmoker, medication-free healthy volunteers from mainland China (n = 323; age: 22.1 ±± 2.0 years) (mean ±± standard deviation), we determined the frequency of polymorphisms in cyclooxygenase 1 ( COX1) (A-842G and C50T), glycoprotein IIIa ( GPIIIa ) (PLA1/A2) and purinergic receptor P2Y ( P2Y1 ) (C893T and A1622G) genes. These candidate genes were chosen on the basis of their impact on platelet physiology and aspirin mode of action. A four panel P2Y1 genotype-stratified sample of healthy volunteers (n = 24 in total), identified from the large study sample above, prospectively received a 100 mg daily oral dose of aspirin for 7 days. We measured changes in platelet aggregation before and after aspirin treatment. As a comparison reference group, 6 out of 24 subjects in the prospective aspirin trial had the P2Y1 CT893/AG1622 genotype that displays a low frequency (<7%) in the Chinese population.Results: COX1 A-842G, C50T and GPIIIa PLA1/A2 genetic polymorphisms were not observed in our sample from mainland China. Allele frequencies of P2Y1 893T and 1622G were 3.5 and 30.6%, respectively. The heterozygosity for the P2Y1 A1622G polymorphism observed in the present study was different to Caucasians; Chinese displayed a higher allele frequency for the 1622G allele. After aspirin treatment, the net decrease in arachidonic acid-induced platelet aggregation was significantly larger in the P2Y1 CT893/AG1622 genotype panel (83.4 ±± 3.7%, net reduction by aspirin expressed as percentage of baseline) compared with CC893/GG1622 (68.2 ±± 13.5%), CC893/AG1622 (68.9 ±± 9.6%) and CC893/AA1622 (65.1 ±± 9.1%) genotypic groups (p = 0.012, 0.025 and 0.004, respectively; statistical power = 77%). There was no significant difference in antiplatelet effect of aspirin among the CC893/GG1622, CC893/AG1622 and CC893/AA1622 genotypes (p > 0.05).Conclusions: The COX1 A-842G, C50T and GPIIIa PLA1/A2 polymorphisms are rare in Chinese. In contrast to previous studies in Caucasian populations, these candidate functional polymorphisms are unlikely to be significant contributors to aspirin pharmacodynamics in Chinese persons. Importantly, the presence of the P2Y1 893CC genotype appears to confer an attenuated antiplatelet effect during aspirin treatment in healthy Chinese volunteers. These data collectively underscore the importance of population-to-population variability in clinical pharmacogenetics research and provide a basis for further long-term studies of aspirin response and P2Y1 genetic variation in patients with cardiovascular risk.